Dermoid cysts causing adnexal torsion: What are the risk factors?. (August 2020) - Rabinovich, Ira; Pekar-Zlotin, Marina; Bliman-Tal, Yael; Melcer, Yaakov; Vaknin, Zvi; Smorgick, Noam
Highlights: Adnexal torsion is diagnosed in ∼20% of women operated for dermoid cysts. Torsion involving dermoid cysts is associated with younger age. Patients with torsion commonly present with nausea and/or vomiting, in addition to abdominal pain. Abstract: Objective: Dermoid cysts (benign mature cystic teratoma) are a relatively common cause of adnexal torsion. We aimed to identify the clinical and surgical characteristics associated with adnexal torsion involving dermoid cysts. Study design: Retrospective review of all cases of ovarian dermoid cysts (as diagnosed by pathology evaluation) operated in our department between 2008−2019. We collected information on demographic characteristics, clinical presentation, and surgical findings and compared those parameters among women with and without adnexal torsion. Results: The study cohort included 231 patients who were operated for ovarian dermoid cysts. Of these, the surgery was performed urgently for suspected adnexal torsion in 77 (33.3%) cases, while adnexal torsion was surgically diagnosed in 51 (22.1%) cases. Diagnosis of torsion was significantly associated with younger mean age (28.8 ± 14.4 years in torsion cases versus 34.5 ± 14.8 years in non-torsion cases, p = 0.01), but not with the mean cyst diameter (81.9 ± 26.3 mm in the torsion group versus 74.7 ± 35.9 mm in the non-torsion group, p = 0.1). Regarding cyst size, torsion was found in women with cyst diameter ≤ 55 mm (9 cases, 17.7% of torsion cases), 60−90 mm (30 cases, 58.8%), and ≥ 100 mm (12 cases, 23.5%) (p = 0.1 for comparison between all groups and p = 0.05 for comparison between the small diameter group versus the intermediate/large diameter groups). Although abdominal pain was reported in most women with and without torsion, patients with adnexal torsion were significantly more likely to present with nausea and/or vomiting (24 cases [47.1%], versus 14 cases [7.8%], respectively, p < 0.001). Conclusion: Torsion of dermoid cysts is associated with younger age, but not with the mean cyst's diameter. Surgical removal of dermoid cysts should be considered in pre-menarchal girls, adolescents and young women to prevent adnexal torsion.